Investigation of Meander Slots To Microstrip Patch Antenna - Zainuddin, N. A; Zakaria, Z; Abd Aziz, M. Z. A; Husain , M. N; Mutalib, M. A (2013)
Microstrip slotted meander line antenna with a diverse number of meander slots is presented for 2.4 GHz of Wireless Local Area Network (WLAN) application. The proposed antenna comprises a rectangular microstrip patch element embedded with several numbers of meander slots in many positions. The parametric study is performed to investigate the characteristic of these microstrip patch antennas with different numbers of meandered slots. Many designs of slotted meander line antenna are produced and they are analyzed based on the number of slotted meander line used. Antenna with 7 slotted meander lines has the most size reduction of approximately 23% of the original size. This study is an early investigation in designing the RF energy harvesting to support green technology and sustainable development particularly for Wireless Sensor Network (WSN) as well as Radio Frequency Identification (RFID) applications.